Examination of the proposed relationships between cyclic menstruation and human reproduction - Vernon G. Thomas (Frontiers in Global Women's Health)
Increased societal food security has enabled frequent ovulation based on women's body fat levels remaining above the fertility threshold. The consequential cyclical menstruation in non-pregnant women constitutes a large female health and welfare issue. This examination of the various roles proposed for menstruation could not detect an essential biological role, whether in the removal of un-implanted embryos or the conditioning of the endometrium against oxidative stress. Neither is menstruation a prerequisite for the regeneration of the uterine endometrium. Menstruation and foetal placental detachment from the endometrium at birth share common hormonally-controlled physiological processes initiated by systemic or local progesterone withdrawal. These critical genetically-conserved processes are essential for the survival of both infant and mother. In human ancestors menstruation likely occurred rarely and these processes were activated only during the birth of several children. Now, because of assured food security, the evolved ancestral function of these processes has been reversed, and even allowing for the birth of several children, a woman may experience hundreds of monthly periods in her life. Menstruation is not necessary for a healthy life and women who control hormonally their periods and fertility still retain the physiological capacity for foetal placental detachment, to be expressed should pregnancy occur. This examination's findings could reduce the ignorance and mis-understanding about menstruation and promote, globally, social policy to reduce “period poverty” and absenteeism of girls and women from schools and the workplace.